Activity of Some Medicinal Plants Against Phytopathogenic Fungi - Sivanandhan, S.; Ganesan, P.; Jackson, A.; Darvin, S.; Paulraj, M.G.; Ignacimuthu, S. (International Journal of Scientific Research in Biological Sciences, 2018)
Crude extracts of 17 medicinal plants were examined for their antifungal properties against phytopathogenic fungi. Hexane, chloroform and methanol extracts were tested using disc diffusion method at concentrations varying from 1.25 to 5 mg/ disc. Among these, hexane extract of Blumea mollis was the most effective against Aspergillus flavus with zone of inhibition of 23mm at 5mg/disc concentration. The Minimal inhibitory concentration (MIC) of B. mollis hexane extract against A. flavus, A. niger and Botrytis cinerea were 0.623, 0.825 and 0.622 mg/ml respectively. Terpenoids, saponins, anthraquinones and anthocyanins were detected in the hexane extract of B. mollis. Subsequently, GC-MS analysis of the extract revealed the main constituent to be cycloheptane (34.21%). This could have potential use as a fungicide against phytopathogens.